Damage patterns in float glass plates: Experiments and peridynamics analysis. (April 2022) - Naumenko, Konstantin; Pander, Matthias; Würkner, Mathias
Abstract: In this study ring bending tests on plates are performed to analyze the tensile strength of tin and air sides of float glass. Fracture stress values computed from experimental data applying the plate theory are analyzed by means of Weibull distribution. Probability of failure vs. fracture stress plots show much higher scatter for the air side than for the tin side. The linear peridynamic solid constitutive model coupled with damage is applied to simulate the ring bending, up to the critical state of crack initiation and early stage of crack propagation. A convergence study with respect to the number of nodes is performed. The simulated sequence of initial damage patterns, including the bond breakage inside the load ring and the formation of ring damage zone followed by initiation of radial cracks agrees with experimental observations for most specimens with tin side subjected to tensile deformation. A novel procedure to identify the critical bond stretch in the damage model based on experimental data for the critical ring force is proposed. The corresponding characteristic values are presented for both tin and air sides of the float glass. Highlights: Fracture strength values for tin and air sides of float glass are determined based on co-axial ring bending tests. Damage patterns in float glass plates are predicted numerically based on the peridynamics. A novel procedure to identify the critical bond stretchin peridynamic damage model from experimental data is proposed.